LA ACTIVIDAD DE LOS VOLCANES DE LA CORDILLERA CENTRAL, COSTA RICA, ENTRE 1998-2002 - Ramírez, Carlos (2011)
The activity of Poás, Barva, Irazú, and Turrialba volcanoes, of the Central Volcanic Range, hasbeen routinely monitored. Monitoring involves seismological, visual, and field observations, such us gas clouds, temperatures and pH from fumaroles, lakes and hot springs and water. The results confirm a chemical and thermal anomaly at the northeast side of the main crater and a high seismic activity in the fault system of Poás. Thevolcanic activity at Irazú and Turrialba has been of fumaroles with temperatures of 80 - 90° C (but one point inTurrialba with T > 90o C), and sporadic seismic events, probably associated with active faulting. Barva is a dor-mant volcano.